STRATEGI PEMBANGUNAN RUMAH LAYAK HUNI (RULAHU) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KABUPATEN JAYAPURA, PROVINSI PAPUA - Agni Grandita Permata Sari (Post Graduate School of Government Science, 2022)
The Residential Housing Development Program is a government program to assist communities in fulfilling their basic needs. This study aims to see how this program is implemented, then the influencing factors, and strategies that can be taken to make this program more optimal. The study used qualitative methods with an inductive approach through data collection techniques of observation, interviews and documentation. The results of this study indicate that the Decent Home program has a positive impact on welfare aspects including material, physical, mental, and spiritual aspects. Then, this study also found that the supporting factors for the implementation of this program were the support from the community, the selection of the right location, and good coordination between the Land, Housing and Settlement Areas Office and the village apparatus. While the inhibiting factors, there are also three things, namely: limited land availability, difficult access to remote areas, and lack of community knowledge about the Rulahu program. The strategy that can be taken by the government based on the results of the SWOT calculation is an offensive approach, including: cooperation with the kelurahan to obtain more valid data on prospective recipients, collaborating with the community for reporting, and improving the quality of house outputs so that people are more confident.